Elezioni nel mondo – Luglio-Dicembre 2004 - Bolgherini, Silvia (Italian Journal of Electoral Studies (IJES), 2005)
Europe: Czeck Republic, Lithuania, Romania, Slovenia, Ukraine; Africa: Botswana, Ghana, Mozambique, Namibia, Niger; Americas: United States, Uruguay; Asia: Japan; Oceania: Australia.